Kinetika Adsorpsi Ion Logam Pb (II) pada Karbon Aktif dengan Gelombang Ultrasonik - Santi, Santi (Al-Kimia, 2015)
Adsorption capacity Increase of the activated carbon can be done with the use of ultrasonic energy-producing high chemical. Activated carbon is used to absorb the metals Pb(II) with a variety of time. Research purposes to determine the effect of variation of contact time on the adsorption of Pb(II) using rice husk activated carbon irradiated with ultrasonic waves and without irradiation. Determining the reaction kinetics model (reaction order and k values) of Pb (II) using rice husk activated carbon irradiated with ultrasonic waves. The results showed the optimum time on the adsorption process of Pb(II) by rice husk activated carbon is irradiated with ultrasonic waves were 50 minutes, whereas the adsorption process of Pb (II) by rice husk activated carbon without irradiated with wave ultrasonic is 30 minutes. Reaction kinetics of Pb(II) according to the pseudo-second-order kinetic model and the value of k2 = 0.0472 g. mg-1.min-1.